IMPLEMENTASI KEBIJAKAN SEKOLAH DALAM PENERAPAN MALCOLM BALDRIGE EDUCATION CRITERIA FOR PERFORMANCE EXCELLENCE DI SD MUHAMMADIYAH 2 GRESIK. - Zakhiroh, Rufqotuz (Program Studi Magister Pedagogi, 2014)
Rufqotuz ZakhirohSD Muhammadiyah 2 Gresike-mail: yufro_zakhiroh@yahoo.comAbstract:This research uses descriptive qualitative method to describe the implementation of the policies of the Baldrige in SD Muhammadiyah 2 Gresik. The Implementation of the Baldrige categories that focus on three categories of Leadership, Workforce Focus, and the Operation Focus. The research results show; 1) aspects of leadership, researcher concluded the Headmaster has a strong enough commitment to direct the school component supports the implementation of policies through the establishment of policy implementation of the Baldrige, communication of policy implementation, continuous improvement, allocation the resources needed. The success of the policy implementation of Baldrige in SD Muhammadiyah 2 Gresik was also supported by the ability of Principals in integrating Baldrige with quality management systems which have already exist such as the Standards of National Education and the International Organization for Standardization (ISO 9001: 2008); 2) From Workforce Focus Categories, the school was able to build a conducive environment for the workforce to achieve high performance. Involving, managing and developing the workforce and taking advantages of all their potentials to be aligned with the vision, mission, strategy, and overall school work programmes; and 3) aspect of Operation Focus, the school is able to design, manage and improve the systems and processes of learning to give value to the students and stakeholders in order to achieve the success and sustainability of the school.Keywords: implementation, policy, malcolm baldrige education, performance excellenceAbstrak:Penelitian ini menggunakan metode kualitatif deskriptif untuk menggambarkan implementasi kebijakan Baldrige di SD Muhammadiyah 2 Gresik. Implementasi Baldrige fokus pada tiga kategori yaitu Kategori Kepemimpinan, Fokus Tenaga Kerja, dan Fokus Operasi. Dari hasil penelitian diperoleh gambaran bahwa 1) dari aspek kepemimpinan, peneliti menyimpulkan Kepala Sekolah memiliki komitmen yang cukup kuat untuk mengarahkan komponen sekolah mendukung implementasi kebijakan Baldrige melalui penetapan kebijakan implementasi, pengkomunikasian kebijakan implementasi, perbaikan terus-menerus, pengalokasian sumber daya yang dibutuhkan. Keberhasilan implementasi kebijakan Baldrige di SD Muhammadiyah 2 Gresik juga didukung oleh kemampuan Kepala Sekolah dalam mengintegrasikan Baldrige dengan system manajemen mutu yang sudah ada di sekolah yaitu Standar Nasional Pendidikan dan International Organization for Standardization (ISO 9001:2008); 2) Dari fokus tenaga kerja, sekolah mampu membangun lingkungan tenaga kerja yang kondusif serta mencapai kinerja tinggi. Sekolah melibatkan, mengelola, dan mengembangkan tenaga kerjanya dan memanfaatkan seluruh potensinya agar selaras dengan misi, strategi, dan program kerja sekolah secara menyeluruh; dan 3) Dari Fokus Operasi, sekolah mampu mendesain, mengelola dan meningkatkan sistem dan proses pembelajaran untuk memberikan nilai pada siswa dan stakeholders guna mencapai keberhasilan dan keberlangsungan sekolah.Kata kunci: implementasi, kebijakan, malcolm baldrige , performance excellence